Analysis and Experimental Study on Dynamic Behavior of Stepper-Actuated Dual-Axis Data Transmission Antenna. (15th April 2021) - Zheng, Zhaomingyue; Cheng, Wei; Li, Ming; Wang, Guangyuan; Tan, Limeng
Abstract : The satellite-borne data transmission antenna is the main disturbing source of low-frequency microvibration of spacecraft, which immensely affects the image quality of remote sensing satellite. In this paper, the dynamic characteristics of flexible load driven by stepping motor on flexible boundary are studied. The dynamic equation of the stepping motor driven by current subdivision is simplified by linearization method. The dynamic model of flexible load driven by stepping motors on flexible boundary is established by using the Dynamic Substructure Method, and the analytical expression of microvibration of the data transmission antenna is given. The coupling relationship between the stepping motors and the flexible structure is analyzed by modal coordinate transformation. The microvibration model is verified by simulation and experiment, and the main causes and coupling factors of microvibration are explained. The results show that the model can accurately predict the microvibration of the satellite antenna and can be applied to the microvibration prediction in orbit. The reasonable selection of the working velocity of the stepping motors can effectively reduce the microvibration, which provides the basis for the design of the antenna control system.